2015 IEEE/ACIS 14th International Conference on Computer and Information Science (ICIS) 2015
DOI: 10.1109/icis.2015.7166666
|View full text |Cite
|
Sign up to set email alerts
|

New adaptive middleware for real-time embedded operating systems

Abstract: The paper presents a middleware implemented in Java, RT-MED, which corresponds to a software layer to be placed above the operating system. This software component is designed to execute and evaluate the performance, reliability and correctness of some real-time scheduling approaches which are theoretically validated. It describes a transition from the theory to the actual implementation of the proposed solutions. These solutions are based on a combinatorial optimization approach to solve the problem of feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Reconfigurable real-time systems have the ability to fully meet the simultaneous performance and flexibility demands [2]. A reconfiguration scenario is usually performed in response to user requirements and dynamic changes in their environment during execution such as unpredictable activation-deactivation-update of some tasks [1], [3], [4]. A scenario of reconfiguration can also be considered as an activation/deactivation of one or more devices when a multi-processor architecture is adopted.…”
Section: Nomenclature Mmentioning
confidence: 99%
“…Reconfigurable real-time systems have the ability to fully meet the simultaneous performance and flexibility demands [2]. A reconfiguration scenario is usually performed in response to user requirements and dynamic changes in their environment during execution such as unpredictable activation-deactivation-update of some tasks [1], [3], [4]. A scenario of reconfiguration can also be considered as an activation/deactivation of one or more devices when a multi-processor architecture is adopted.…”
Section: Nomenclature Mmentioning
confidence: 99%
“…The work reported in [160] extended to [161] optimizes the execution frequency of tasks to meet related constraints. These solutions are encoded in a middleware above operating system as reported in [162]. The research reported in [163] proposes a new multi-agent architecture for securing reconfigurable systems.…”
Section: A Monoprocessor Scheduling Of Reconfigurable Tasks Under Enmentioning
confidence: 99%